Hiperglikemia dan Komplikasi Akut Diabetes Mellitus - Ahmad H Asdie Ahmad H Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
Diabetes mellitus is a chronic metabolic disorder due to relative or absolute deficiency of insulin. The disease may be characterized by acute symptoms and signs of insulin deficiency, which are called acute complications in this paper. Diabetes is also associated with chronic complications such as atherosclerosis, neuropathy, nephropathy, retinopathy, and' cataract. The paper presented a brief review of the role of hyperglycemia in the development of complic ations in the diabetic patient. There is little controversy as to the necessity of insulin for therapy and for prevention of diabetic complications. Key Words: diabetes mellitus - insulin deficiency - hyperglycemia - metabolic disorder - lipoprotein